Antenatal Diagnosis and Surgical Management of Cpam: A Case-Based Approach - Shanmugam, Karthikeyan; P, Jai Durairaj; C, Anusuya; Murali, Keerthika (Journal of Neonatal Surgery, 2025)
Introduction Congenital Pulmonary Adenomatoid Malformation (CPAM, formerly Congenital Cystic Adenomatoid Malformation (CCAM) is an uncommon but clinically relevant malformation of the lung. The incidence of CPAM is estimated to range from 1:25,000 and 1:35,000 live births, representing 25% of all diagnosed congenital pulmonary malformations. Case presentation A 30 year old antenatal mother at 21 weeks of gestation came for anomaly scan and was diagnosed with mixed type, left CPAM with midline shift to right side, CPAM volume ratio 0.475. The child was followed up and presented as a 5-month-old male with antenatally diagnosed CPAM (Type 1) of the left lung presented with a 2-month history of intermittent cough and cold. Born at term via LSCS to a mother with gestational diabetes, he had transient neonatal respiratory distress. Clinical examination revealed reduced air entry in the left upper zones. Imaging showed a growing cystic lesion with mediastinal shift. At 4 months, CT confirmed a 4.8 × 4.4 × 4.5 cm Type 1 CPAM. Elective thoracotomy with left upper lobectomy was performed. Histopathology confirmed CPAM Type 1. Postoperative recovery was uneventful, with full lung re-expansion and discharge on POD 7. Discussion This case emphasizes the necessity of the multidisciplinary approach that includes the pediatrician, radiologist,obstretician, surgeon and pathologist in order to achieve the best outcome. Early detection, follow up, appropriate surgical resection and adequate histopathological assessment are essential in the management of Congenital Pulmonary Adenomatoid Malformation. Conclusion This case highlights the importance of early recognition, close monitoring, prenatal diagnosis, follow-up and proper treatment of Congenital Pulmonary Adenomatoid Malformation